Macroeconomic effects of a low carbon electrification of greater Kampala Metropolitan area energy policy: A computable general equilibrium analysis - Kimuli, Ismail; Lubwama, Michael; Sebbit, Adam; Kirabira, John Baptist (Energy Strategy Reviews, 2022)
Greater Kampala Metropolitan Area (GKMA) is Uganda’s capital facing increasing pressures to raise electricity generation and also mitigate CO2 emissions. A low-carbon electrification of the GKMA energy policy is proposed for sustainability. But the macroeconomic effects of this policy are unknown. The study uses a multi-sector, single region, static GKMA-CGE model to address the knowledge gap in 4 scenarios. BAU is the baseline against which comparisons with Kabejja (20% CO2 abatement); Carbon-Tax ($100/ton) and Lutta scenarios (95% CO2 abatement) are made. The results indicate GDP increased by Kabejja:0.7%; Carbon-Tax:1.3%; Lutta:1.56% with respect to BAU. Equivalent variation also increased compared to BAU. Energy & CO2 intensities of GDP decreased in all scenarios. The study recommends Lutta for a sustainable 2050.
Keywords: Sustainability; Energy scenarios; Static CGE modeling; Low-carbon electrification